A proposal to increase employee performance through employee engagement survey in pt KBI - Harvid, Albertus; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2013)
PT. Karunia Berca Indonesia (KBI) is one of the best steel galvanizing factory in Indonesia. KBI have some problems like lack of willingness to train, lack of employee development program, and lack of facilities. That 3 factors are performance indicator. Low on employee performance will decrease the revenue. With root cause analysis can be found the main problem in PT KBI is lack of performance. To increase employee performance, KBI must determine the engagement for the employee using employee engagement survey. The survey composition is a synthesis from ASTD Gallup, and DDI. After collecting, the questionnaire data, the analyzed is done with SPSS program. The results are determining 2 main problem about engagement in PT. KBI, there are, receive adequate resources variable, and Efficient work Environment (culture) variable. Deeper interview for 2 main problem is done with some staff in PT. KBI. Interview result about receive adequate resources, KBI is lacking Indoor area for painting and wielding, and the storage capacity. The second problem is about training habit. KBI want every employee to go training, but the employee think training is wasting time. The solution for the first problem are adding roof for outdoor activity and expanding the area for storage. The solution for the second problem is, creating champion to help brainstorming the other employee about training.Â Keywords: Employee engagement, training , Change management, employee performance